Is the Discount Rate Relevant in Explaining the Environmental Kuznets Curve? - Giuseppe Di Vita (Fondazione Eni Enrico Mattei (FEEM), 2003)
In this paper we use Pindyck's model (2002) to show that the discount rate may play an important role in explaining for the income-pollution pattern observed in the real world. Low levels of income involve high values of discount rate, that are obstacles to the adoption of a pollution abatement policy. Only when the discount rate falls, as a consequence of growth, will it be possible to implement measures for emissions reduction. Thus we are able to derive an inverse U-shaped income-pollution pattern, making use of an argument that has never yet been introduced in the economic debate on this issue.
Keywords: Q2; D61; 330; Discount rate; Environmental Kuznets Curve; Income; Stock pollutants; Umweltbelastung; Nationaleinkommen; Diskontierung; Theorie; Environmental Kuznets Curve